Car Mechanics in the Lab - Investigating the Behavior of Real Experts on Experimental Markets for Credence Goods - Adrian Beck; Rudolf Kerschbamer; Jianying Qiu; Matthias Sutter (University of Innsbruck, Department of Public Finance, 2009)
We compare the behavior of car mechanics and college students as sellers in experimental credence goods markets. Finding largely similar behavior, we note much more overtreatment by car mechanics, probably due to decision heuristics they learned in their professional training.
Keywords: C91; D82; C72; 330; Artefactual field experiment; Car mechanics; Credence goods; Nichtkooperatives Spiel; Kraftfahrzeugtechnische Berufe; Studierende; Asymmetrische Information; Test